Your SlideShare is downloading. ×
  • Like
CPSC 125 Ch 1 sec 4
Upcoming SlideShare
Loading in...5
×

Thanks for flagging this SlideShare!

Oops! An error has occurred.

×

Now you can save presentations on your phone or tablet

Available for both IPhone and Android

Text the download link to your phone

Standard text messaging rates apply

CPSC 125 Ch 1 sec 4

  • 973 views
Published

 

Published in Technology , Education
  • Full Name Full Name Comment goes here.
    Are you sure you want to
    Your message goes here
    Be the first to comment
    Be the first to like this
No Downloads

Views

Total Views
973
On SlideShare
0
From Embeds
0
Number of Embeds
0

Actions

Shares
Downloads
24
Comments
0
Likes
0

Embeds 0

No embeds

Report content

Flagged as inappropriate Flag as inappropriate
Flag as inappropriate

Select your reason for flagging this presentation as inappropriate.

Cancel
    No notes for slide

Transcript

  • 1. Formal Logic Mathematical Structures for Computer Science Chapter 1 Copyright © 2006 W.H. Freeman & Co. MSCS Slides Formal Logic
  • 2. Predicate Logic ●  Similar to propositional logic for solving arguments, build from quantifiers, predicates and logical connectives. ●  A valid argument for predicate logic need not be a tautology. ●  The meaning and the structure of the quantifiers and predicates determines the interpretation and the validity of the arguments ●  Basic approach to prove arguments: ■  Strip of quantifiers ■  Manipulate the unquantified wffs ■  Reinsert the quantifiers Four new inference rules Two rules to strip the qualifiers Two rules to reinsert the qualifiers ●  Note to remember: P(x) could be (∀y) (∀z) Q(x,y,z) Section 1.4 Predicate Logic 1
  • 3. Inference Rules From Can Derive Name / Restrictions on Use Abbreviation (∀x)P(x) P(t) where t is a Universal If t is a variable, it must variable or constant Instantiation- ui not fall within the scope symbol of a quantifier for t (∃x)P(x) P(t) where t is a Existential Must be the first rule variable or constant Instantiation- ei used that introduces t symbol not previously used in a proof sequence P(x) (∀x)P(x) Universal P(x) has not been Generalization- ug deduced from any hypotheses in which x is a free variable nor has P (x) been deduced by ei from any wff in which x is a free variable P(x) or P(a) (∃x)P(x) Existential To go from P(a) to (∃x)P Generalization- eg (x), x must not appear in P(a) Section 1.4 Predicate Logic 2
  • 4. Examples: Proofs using Predicate Logic ●  Prove the following argument: ■  All flowers are plants. Sunflower is a flower. Therefore, sunflower is a plant. ■  P(x) is “ x is a plant” ■  a is a constant symbol (Sunflower) ■  Q(x) is “x is a flower” ●  The argument is (∀x)[Q(x) → P(x)] Λ Q(a) → P(a) ●  The proof sequence is as follows: 1.  (∀x)[Q(x) → P(x)] hyp 2.  Q(a) hyp 3.  Q(a) → P(a) 1, ui 4.  P(a) 2, 3, mp Section 1.4 Predicate Logic 3
  • 5. Examples: Proofs using Predicate Logic ●  Prove the argument (∀x)[P(x) → Q(x)] Λ [Q(y)]ʹ′ → [P(y)]ʹ′ ●  Proof sequence: 1.  (∀x)[P(x) → Q(x)] hyp 2.  [Q(y)]ʹ′ hyp 3.  P(y) → Q(y) 1, ui 4.  [P(y)]ʹ′ 2, 3, mt ●  Prove the argument (∀x)P(x) → (∃x)P(x) ●  Proof sequence: 1.  (∀x)P(x) hyp 2.  P(x) 1, ui 3.  (∃x)P(x) 2, eg Section 1.4 Predicate Logic 4
  • 6. Examples: Proofs using Predicate Logic ●  Prove the argument (∀x)[P(x) → Q(x)] Λ (∀x)P(x) → (∀x)Q(x) ●  Proof sequence: 1.  (∀x)[P(x) → Q(x)] hyp 2.  (∀x)P(x) hyp 3.  P(x) → Q(x) 1, ui 4.  P(x) 2, ui : no restriction on ui about reusing a name 5.  Q(x) 3, 4, mp 6.  (∀x)Q(x) 5, ug ●  Note: step 6 is legitimate since x is not a free variable in any hypothesis nor was ei used before Section 1.4 Predicate Logic 5
  • 7. Examples: Proofs using Predicate Logic ●  Prove the argument (∀x)[P(x) Λ Q(x)] → (∀x)P(x) Λ (∀x)Q(x) ●  Proof sequence: 1.  (∀x)[P(x) Λ Q(x)] hyp 2.  P(x) Λ Q(x) 1, ui 3.  P(x) 2, sim 4.  Q(x) 2, sim 5.  (∀x)P(x) 3, ug 6.  (∀x)Q(x) 4, ug 7.  (∀x)P(x) Λ (∀x)Q(x) 5, 6, con Section 1.4 Predicate Logic 6
  • 8. Examples: Proofs using Predicate Logic ●  Prove the argument (∀y)[P(x) → Q(x,y)] → [P(x) → (∀y)Q(x,y)] ●  Using the deduction method, we can derive (∀y)[P(x) → Q(x,y)] Λ P(x) → (∀y)Q(x,y) ●  Proof sequence: 1.  (∀y)[P(x) → Q(x,y)] hyp 2.  P(x) hyp 3.  P(x) → Q(x,y) 1, ui 4.  Q(x,y) 2, 3, mp 5.  (∀y)Q(x,y) 4, ug Section 1.4 Predicate Logic 7
  • 9. Temporary hypotheses ●  A temporary hypothesis can be inserted into a proof sequence. If T is inserted as a temporary hypothesis and eventually W is deduced from T and other hypotheses, then the wff T → W has been deduced from other hypotheses and can be reinserted into the proof sequence ●  Prove the argument [P(x) → (∀y)Q(x,y)] → (∀y)[P(x) → Q(x,y)] ●  Proof sequence: 1.  P(x) → (∀y)Q(x,y) hyp 2.  P(x) temporary hypothesis 3.  (∀y)Q(x,y) 1, 2, mp 4.  Q(x,y) 3, ui 5.  P(x) → Q(x,y) temp. hyp discharged 6.  (∀y)[P(x) → Q(x,y)] 5, ug Section 1.4 Predicate Logic 8
  • 10. More Examples ●  Prove the sequence [(∃x)A(x)]ʹ′ ⇔ (∀x)[A(x)]ʹ′ ■  To prove equivalence, implication in each direction should be proved ●  Proof sequence for [(∃x)A(x)]ʹ′ → (∀x)[A(x)]ʹ′ 1.  [(∃x)A(x)]ʹ′ hyp 2.  A(x) temp. hyp 3.  (∃x)A(x) 2, eg 4.  A(x) → (∃x)A(x) temp. hyp discharged 5.  [A(x)]ʹ′ 1, 4, mt 6.  (∀x)[A(x)]ʹ′ 5, ug ●  Proof sequence for (∀x)[A(x)]ʹ′ → [(∃x)A(x)]ʹ′ 1.  (∀x)[A(x)]ʹ′ hyp 2.  (∃x)A(x) temp. hyp 3.  A(a) 2, ei 4.  [A(a)]ʹ′ 1, ui 5.  [(∀x)[A(x)]ʹ′]ʹ′ 3, 4, inc 6.  (∃x)A(x) → [(∀x)[A(x)]ʹ′]ʹ′ temp. discharged 7.  [((∀x)[A(x)]ʹ′)ʹ′]ʹ′ 1, dn 8.  [(∃x)A(x)]ʹ′ 6, 7, mt Section 1.4 Predicate Logic 9
  • 11. Proving Verbal arguments ●  Every crocodile is bigger than every alligator. Sam is a crocodile. But there is a snake, and Sam isn’t bigger than that snake. Therefore, something is not an alligator. ■  Use C(x): x is a crocodile; A(x): x is an alligator, B(x,y): x is bigger than y, s is a constant (Sam), S(x): x is a Snake ●  Hence prove argument (∀x) (∀y)[C(x) Λ A(y) → B(x,y)] Λ C(s) Λ (∃x)(S(x) Λ [B(s,x)]ʹ′) → (∃x)[A(x)] 1.  (∀x) (∀y)[C(x) Λ A(x) → B(x,y)] hyp 2.  C(s) hyp 3.  (∃x)(S(x) Λ [B(s,x)]ʹ′) hyp 4.  (∀y)[C(s) Λ A(y) → B(s,y)] 1, ui 5.  S(a) Λ [B(s,a)]ʹ′) 3, ei 6.  C(s) Λ A(a) → B(s,a) 4, ui 7.  [B(s,a)]ʹ′ 5, sim 8.  [C(s) Λ A(a)]ʹ′ 6, 7, mt 9.  [C(s)]ʹ′ V [A(a)]ʹ′ 9, De Morgan 10.  [[C(s)]ʹ′]ʹ′ 2, dn 11.  [A(a)]ʹ′ 9, 10, ds 12.  (∃x)[A(x)]ʹ′ 11, eg Section 1.4 Predicate Logic 10
  • 12. Class Exercise ●  Prove the argument (∀x)[(B(x) V C(x)) → A(x)] → (∀x)[B(x) → A(x)] Proof sequence: 1.  (∀x)[(B(x) V C(x)) → A(x)] hyp 2.  (B(x) V C(x)) → A(x) 1, ui 3.  B(x) temp. hyp 4.  B(x) V C(x) 3, add 5.  A(x) 2, 4, mp 6.  B(x) → A(x) temp. hyp discharged 7.  (∀x)[B(x) → A(x)] 6, ug Section 1.4 Predicate Logic 11
  • 13. Class exercise ●  Every ambassador speaks only to diplomats, and some ambassadors speak to someone. Therefore, there is a diplomat. ●  Use A(x): x is an ambassador; S(x,y): x speaks to y; D(x): x is a diplomat Prove the argument (∀x) (∀y)[(A(x) Λ S(x,y)) → D(y)] Λ (∃x)(∃y)(A(x) Λ S(x,y)) → (∃x)D(x) Proof Sequence: 1.  (∀x) (∀y)[(A(x) Λ S(x,y)) → D(y)] hyp 2.  (∃x)(∃y)(A(x) Λ S(x,y)) hyp 3.  (∀y)((A(a) Λ S(a,y)) → D(y)) 1, ui 4.  (∃y)(A(a) Λ S(a,y)) 2, ei 5.  A(a) Λ S(a,b) 4, ei 6.  (A(a) Λ S(a,b)) → D(b) 3, ui 7.  D(b) 5, 6, mp 8.  (∃x)D(x) 7, eg Section 1.4 Predicate Logic 12